Pendekatan Penilaian Autentik Berbasis Digital dalam Evaluasi Pembelajaran Anak Usia Dini - Dwi Nomi Pura; Mimpira Haryono; Adefia Marsa Gella; Dhera Calista Febriana; Rennia Syfutri (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Evaluation in early childhood education plays an important role in understanding children's developmental progress comprehensively. One of the approaches that can be applied is authentic assessment, which evaluates children's abilities through real activities carried out during the learning process. Along with the rapid development of information technology, the implementation of authentic assessment has begun to integrate digital technology to support the evaluation process. This study aims to analyze the implementation and benefits of digital-based authentic assessment in evaluating early childhood learning. The research uses a qualitative descriptive approach with a literature study method. Data were obtained from various scientific sources, including academic books, national and international journal articles, and research reports related to authentic assessment and the use of digital technology in early childhood education. Data collection was carried out through documentation and literature review, while data analysis used content analysis techniques to identify concepts, patterns, and relationships among the reviewed literature. The results of the study indicate that digital-based authentic assessment provides several advantages in evaluating early childhood learning. The use of digital media such as photos, videos, audio recordings, and digital portfolios enables teachers to document children's learning activities more systematically and accurately. In addition, digital systems facilitate the storage, organization, and monitoring of children's developmental data continuously. Digital-based assessment also encourages greater parental involvement because parents can access information about children's learning progress more transparently. However, its implementation still faces several challenges, such as teachers' digital competence and the availability of technological infrastructure in early childhood education institutions. Therefore, support in the form of teacher training and adequate technological facilities is needed to optimize the implementation of digital-based authentic assessment.